ANALYSIS OF LAYOUT SCHEMES OF SLEEPING CARS - Voytkiv, S. V. (Science and Transport Progress, 2020)
Purpose. The purpose of the work is the development, analysis and selection of layout schemes for passenger cars according to the number and location of enclosed platforms and sanitary facilities for creating promising competitive sleeping cars of various comfort levels and assessing the prospects of mastering their mass production in terms of ensuring maximum capacity. Methodology. An analysis of the layout schemes and planning of existing sleeping cars of various European manufacturers and layout schemes of promising cars in terms of size, number and placement of enclosed platforms and sanitary facilities was carried out according to the proposed criteria and performance for the efficiency of design solutions and the comfort of cars. Findings. Designed layout schemes of promising sleeping cars equipped with two or one enclosed platform and three or four sanitary facilities for general use – lavatory rooms, lavatory rooms combined with shower racks or shower cabins and separate shower cabins. A technique is proposed for assessing the efficiency of the developed design solutions and the comfort of promising sleeping cars in terms of the number, purpose and location of sanitary facilities and the ease of their use by passengers. Based on the analysis of the proposed layout schemes, their optimal variants were selected, recommended for creating promising competitive sleeping cars of a substantially higher comfort level. Originality. For the first time, an analysis of existing and new layout schemes of passenger sleeping cars by the number and placement of enclosed platforms and the number, types and placement of public sanitary facilities based on the developed methodology for an objective assessment of the efficiency of layout solutions, levels of car comfort and ease of their use by passengers. Practical value of the work lies in the possibility of a reasonable choice already at the stage of development of outline proposals for optimal layout schemes for creating promising competitive sleeping cars of different classes of increased comfort levels.